Capital Gay : a weekly newspaper for lesbians and gay men. (London : Stonewall Press, 1982)
Fonds Suzan Daniel (FSD)
Periodiciteit : wekelijks
Redactie: 1 Tavistock Chambers, Bloomsbury Way, London WC1A 2SE
Engels
Periodiek